Multiple endocrine neoplasia syndrome in a 6-year-old child. - Mun, A.V.; Kuddusova, K.K.q. (European Journal of Pediatric Dermatology, 2025)
Multiple endocrine neoplasia (MEN) syndromes comprise a group of autosomal dominant hereditary disorders characterized by specific clinical features driven by excessive hormonal secretion. The parathyroid glands, thyroid, adrenal glands, pituitary, and pancreatic islet cells may be involved. The most serious complication is the development of potentially life-threatening neoplasms of these glands, which can be diagnosed early – and in some cases prevented – thanks to subtle cutaneous and mucosal manifestations, as illustrated in the case of a 6-year-old child described herein.